Danny the dragon - Punter, Russell; Cottrill, Peter (Tulsa, Okla. : EDC Pub., 2009)
Danny, a friendly dinosaur who helps the villagers by starting fires, cooking food, and lighting candles, no longer feels needed after a peddler comes to town selling magic fire sticks, but he learns there is more he can do when a gang of robbers arrives.
2.1
K-3
Keywords: Dragons -- Juvenile fiction; Helping behavior -- Juvenile fiction; Thieves -- Juvenile fiction; Dragons -- Fiction; Helpfulness -- Fiction; Robbers and outlaws -- Fiction; Dragons -- Fiction; Helping behavior -- Fiction; Thieves -- Fiction; Readers (Elementary).